2014
DOI: 10.3109/14767058.2014.916676
|View full text |Cite
|
Sign up to set email alerts
|

What is the impact of SOCS3, IL-35 and IL17 in immune pathogenesis of recurrent pregnancy loss?

Abstract: Decreased SOCS3 and IL-35 plasma levels and increased Th1/Th2 cytokine ratios in RPL cases pointed out the supression of anti-inflammatory process and this supression might play an important role in the pathogenesis of idiopathic RPL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 37 publications
1
22
1
Order By: Relevance
“…Women with a history of idiopathic recurrent pregnancy loss (RPL) showed lower levels of plasma IL‐35 in comparison to fertile women without a history of RPL. In addition, these women had a higher level of plasma IL‐17, which adversely affects the success of pregnancy and can be down‐regulated by IL‐35 . Although the fundamental mechanisms of IL‐35 function in reproduction are not clear, it has been confirmed that serum IL‐35 levels are elevated in normal pregnancy and correlate with increased estrogen and alpha‐fetoprotein (AFP) levels in early pregnancy.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Women with a history of idiopathic recurrent pregnancy loss (RPL) showed lower levels of plasma IL‐35 in comparison to fertile women without a history of RPL. In addition, these women had a higher level of plasma IL‐17, which adversely affects the success of pregnancy and can be down‐regulated by IL‐35 . Although the fundamental mechanisms of IL‐35 function in reproduction are not clear, it has been confirmed that serum IL‐35 levels are elevated in normal pregnancy and correlate with increased estrogen and alpha‐fetoprotein (AFP) levels in early pregnancy.…”
Section: Resultsmentioning
confidence: 99%
“…However, studies on IL‐35 in human pregnancy and in reproduction field are limited. Thus far, IL‐35 levels have been studied mainly in the serum and trophoblasts of pregnant women or peritoneal fluid and endometrial tissue of women with endometriosis . In addition, IL‐35 was tested in the decidua of women after delivery.…”
Section: Resultsmentioning
confidence: 99%
“…Accordingly, IL‐35 is necessary for maintaining testicular immune privilege . Moreover, IL‐35 may also contribute to fetal–maternal tolerance during pregnancy …”
Section: Immune‐regulation and The Dilemma Of Treatment Of Chronic Inmentioning
confidence: 99%
“…Given the implication of immune-regulation in the development of maternal-fetal tolerance, lack of immuneregulation is considered as a newly suggested potential etiological cause of recurrent pregnancy losses (RPL). 77 Approximately 50% of RPL incidences are classified as idiopathic. 81 Accumulating data on dysregulation of immune tolerance in conjunction with RPLs might drive the discovering of new targets to prevent RPL.…”
Section: Il-35 An Immune-regulatory Marker In Pregnancymentioning
confidence: 99%
See 1 more Smart Citation